Acceptance in principle, contestation in practice: EU norms and their discontents in Tunisia. Issue 3 (3rd April 2022) - Weilandt, Ragnar
ABSTRACT: The EU's institutional, civic and social as well as economic norms enjoy comparably high levels of support in Tunisia. However, there are differences with regards to how individual of these three sets of norms resonate with different parts of Tunisian society and elites. This article examines their acceptance, modification and contestation by Islamists, secular conservatives and secular progressives within Tunisia. It finds that almost all EU norms are supported by some parts of Tunisian society and elites, but are also all, to some extent, contested by others. This is strongly shaped by previous domestic experiences and by ideas that evolved within Tunisia. The article thus argues that the extent to which external norms are adopted in law and practice primarily depends on local agency. Moreover, the extent to which EU norms are accepted as well as the openness to competing norms are linked to output legitimacy. Perceived inabilities of Tunisia's post-2011 system to deliver socio-economic gains, improvements to the security situation or legislation that reflects peoples' preferred values tend to go hand in hand with contestation of the model promoted by the EU.